The value of a screen and treat policy for Chlamydia trachomatis in women attending for termination of pregnancy. Issue 2 (1st April 2001) - Groom, Tamsin M; Stewart, Peter; Kruger, Heike; Bell, Gill
Abstract : We aimed to assess the efficacy of a screen and treat policy for sexually transmitted infections in women requesting termination of pregnancy, with particular reference to Chlamydia trachomatis . A retrospective review of 100 consecutive cases of Chlamydia -positive women between December 1995 and February 1998, was performed. The referral rate to genitourinary medicine (GUM), the subsequent management, contact tracing and treatment of partners were assessed. Ninety-nine women were referred to the GUM department, of whom 72 (71.4%) attended. Eighteen (25%) required further treatment. Seventy-five women identified 89 potentially infected men, of whom 62 (69%) attended for treatment. Identification of positive cases with referral to GUM enabled tests of cure to be carried out, treatment of those reinfected and re-enforcement of behaviour modification, in addition to successful contact tracing. This policy may confer greater benefit for the patient herself and make a significant impact on the reservoir of infection in the community when compared to a policy of blanket prophylactic antibiotic treatment at the time of termination. The implications for future service provision are discussed.